Macroeconomic vulnerability and disagreement in expectations - Cristian Badarinza; Marco Buchmann (European Central Bank (ECB), 2011)
In this paper we discuss the role of the cross-sectional heterogeneity of beliefs in the context of understanding and assessing macroeconomic vulnerability. Emphasis lies on the potential of changing levels of disagreement in expectations to influence the propensity of the economy to switch between different regimes, a hypothesis that finds robust empirical support from a regime-switching model with endogenous transition probabilities for output growth and realized stock market volatility in the US.
Keywords: C53; D8; E32; 330; business cycles; endogenous transition probabilities; forecasting; Heterogeneous beliefs; regime-switching